Polyurethane Binder For Mxene Electrode Fabrication Of Hybrid Supercapacitor - Zurainee, Nurul Izzaty (Universiti Sains Malaysia, 2022)
Polyurethane (PU) binder was combined with titanium carbide (TiC) and activated carbon utilising N-methyl-2pyrrolidone (NMP) as a solvent to generate TiC-PU based supercapacitor electrode (SC). The slurry with different wt% of which are TiC-PU 2 wt%, 4 wt%, 6 wt%, 8 wt% and 10 wt%. After stirring PU for 10 minutes in 5ml NMP, TiC and AC were added and mixed for 2 hours at RT. After that, the slurry was dipped on Nickel (Ni) foam in 1 x 1 cm2 and dried for 3 hours at RT before oven-drying at 80oC overnight this step was repeated on second day, making the TiC-PU electrode twice dipped-dried. The morphology shows that TiC-PU 10 wt% has a good TiC surface distribution on Ni foam and more uniform on Ni foam compared to the other composition of TiC-PU. Also, XRD plot shows that Ni peak by TiC-PU 10 wt% has the lowest intensity which proved that PU binder formed a great physical bond and spread-ability. Same goes to electrochemical characteristic shows that, TiC-PU 10 wt% displays a good redox behaviour and exhibited high specific capacitance for CV which is 0.00124 F g-1 at scan rates of 10 mV s-1. The specific capacitance by TiC-PU binders was 10 wt % > 8 wt % > 6 wt % > 4 wt % > 2 wt %. The greater amount of PU binder reduces the TiC active site and, as a result, the specific capacitance. The sequence of specific capacitance by TiC-PU binders from GCD curves was 10 wt % > 8 wt % > 6 wt % > 4 wt % > 2 wt %, with TiC-PU 10 wt % showing the maximum specific capacitance of 81.9076 F g-1 at current density of 1.4 A g-1. This revealed that the TiC-PU 10 wt% appeared to be a promising electrode material for supercapacitor applications compared to the other wt% of TiC-PU electrode.